2018
DOI: 10.3390/w10121721
|View full text |Cite
|
Sign up to set email alerts
|

An Improvement of Port-Hamiltonian Model of Fluid Sloshing Coupled by Structure Motion

Abstract: The fluid–solid interaction is an interesting topic in numerous engineering applications. In this paper, the fluid–solid interaction is considered in a vessel attached to the free tip of a cantilever beam. Governing coupled equations of the system include the Euler–Bernoulli equation for bending of a beam, torsion of a beam, 2-D motion of the rigid vessel, and rotating shallow water equation of fluid sloshing in the vessel. As an essential portion in the numerical simulation of the vibration control of this fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Jamalabadi studied sloshing in flexible tanks induced by an earthquake using a one-way coupling of the finite element model (FEM) and CFD techniques. He found that the elasticity of the walls increased impulsive pressure [29]. Veletsos and Tang [30] studied the effects of soil-structure interaction on ground-level cylindrical tanks.…”
Section: Introductionmentioning
confidence: 99%
“…Jamalabadi studied sloshing in flexible tanks induced by an earthquake using a one-way coupling of the finite element model (FEM) and CFD techniques. He found that the elasticity of the walls increased impulsive pressure [29]. Veletsos and Tang [30] studied the effects of soil-structure interaction on ground-level cylindrical tanks.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [36] and Sun et al [37] performed classical nonlinear works on sloshing while the nonlinearity refers to the fluid part. Jamalabadi [38,39] solved the FSI problem in analytical sloshing, sloshing with the improved boundary layer approximation [40], sloshing with finite element [41,42], LBM [43], and sloshing with SPH method [44]. In many of studies a linear elastic model is adopted for solid part and focus of accuracy is on fluid section [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the problem of fluid-structure in sloshing is studied in many types of research by port-Hamiltonian approach (Abdollahzadeh Jamalabadi, 2018), analytical method (Abdollahzadeh Jamalabadi, 2019), entropy generation minimization method (Jamalabadi, 2019), passive control with baffles (Jamalabadi et al, 2018), vibration suppression method (Jamalabadi, 2020), smoothed particle hydrodynamics method (Abdollahzadeh Jamalabadi, 2020b), active control by piezoelectric sheets (Abdollahzadeh Jamalabadi, 2020a), and experimental methods (Gorman et al, 2001). The case simply is similar to an Indian musical drum with respect to the case of vibroacoustic effects involving a circular plate; however, the fluid in the container is assumed here to be incompressible and inviscid.…”
Section: Introductionmentioning
confidence: 99%